The changing role of the state and market in low cost housing provision in Malaysia - Shuid, Syafiee (Kulliyyah of Architecture and Environmental Design, IIUM, 2011)
Since 1990s the global trend in housing provision shows a shift towards greater market role including for low income housing. Increasingly the state relied on market to provide low income housing and confined its role as enabler and facilitator to support the market. Housing provision refers to process of housing production and consumption or allocation by the consumers. Thus, the analysis in this paper focused on the role of the state and market in low cost housing production and allocation process. The findings showed the state gradually began to retreat from direct low cost housing provision and relied on market since 1990s. Despite economic crisis in 1997-1998 the market still played significance role in low cost housing production. Instead the state focused on solving housing problem among the squatters and revived the economy through public housing programmes. However in terms of low cost housing allocation, the state still retained it controlled since 1950s. Thus, explained the unique features of low cost housing provision system in Malaysia.